A novel behavioral science-based health checkup program and subsequent metabolic risk reductions in a workplace: Checkup championship. - Nagata, Hanae; Sato, Koryu; Haseda, Maho; Kobayashi, Yumiko; Kondo, Naoki (Preventive Medicine, 2022)
The effectiveness of general health checkups and lifestyle counseling has been questioned. This study examined whether a workplace health promotion program implemented during a health checkup was associated with metabolic syndrome-related indicators. Hakuhodo DY group, one of Japan's largest advertising agencies, implemented a behavioral science-based program called "Checkup Championship" (Kenshin-sen in Japanese) in 2019, in which all employees could voluntarily participate. We studied 3697 employees (2818 men and 879 women, mean age: 40.7 years), consisting of 1509 program participants and 2188 non-participants. The characteristics of participants and non-participants were balanced using inverse probability weighting. We used their data from the health checkups in 2018 and 2019 together with other covariates and performed a difference-in-differences analysis using a linear mixed model. After program implementation, greater reductions were observed among participants compared with non-participants in weight (-0.66 kg, 95% confidence interval: -0.84 to -0.47), body mass index (-0.23 kg/m2, -0.29 to -0.16), waist circumference (-0.67 cm, -0.91 to -0.43), systolic blood pressure (-1.13 mmHg, -2.10 to -0.16), and diastolic blood pressure (-0.84 mmHg, -1.53 to -0.15). In addition, we observed greater reductions in weight, body mass index, waist circumference, and low-density lipoprotein cholesterol among participants who were with two or more risk factors for metabolic syndrome than other participants. We found that participation in a health checkup program based on behavioral science was associated with reduced metabolic syndrome-related indicators. There may be room for improvement in the effectiveness of general health checkups.